(untitled) (American Journal of Islam and Society, 2002)
Written by a professor oflslamic Studies at Hartford Seminary in Connecticut, ls/am in America introduces the history and practice of Islam in the United States. The book opens with an overview of the origins and historical development of Islam that for the most part is fair, although there is the odd error ("Throughout the centuries, the call to prayer has been sung ..." Some of the figures mentioned in Chapter 2, "Contributors to the Development of Islam" also cause eyebrows to be raised: how much the secularist Mustafa Kemal contributed to the development oflslam is surely debatable. Moving on to the American context (Chapter 3), the author starts her exploration oflslamic history in the US with the waves of immigration from Muslim lands that began in the middle and latter part of the nineteenth cen tury. Pre-Columbian visits to these shores by Muslims are touched upon, but it is noted that this is a new area of scholarship. The issue of Muslim slaves brought by force from Africa is dealt with later, in the chapter on AfricanAmerican Islam. The issues faced by the earliest immigrants are touched upon, and a brief history oflslam in several major centers is given. Accounts of minority groupings - Sh????a, Sufis, Isma>il is, Druze, and Ahmad is- are also given. Whether all of these groupings are "truly Islamic" or not is a moot point, however, the fact that they are connected to or have roots in the Islamic tradition means that they are often included in studies of Islam, particularly studies written by western observers. While stating that the majority of Muslims in the US are either immigrants or African-Americans, the author notes that there are significant numbers of converts from other backgrounds too; mention is made of Anglos, Hispanics and Native Americans who have come to Islam ...